2022
DOI: 10.1111/jcmm.17339
|View full text |Cite
|
Sign up to set email alerts
|

Incredible affinity of Kattosh with PPAR‐γ receptors attenuates STZ‐induced pancreas and kidney lesions evidenced in chemicobiological interactions

Abstract: Since ancient times, plants have been used as green bioresources to ensure a healthier life by recovering from different diseases. Kattosh (Lasia spinosa L. Thwaites) is a local plant with various traditional uses, especially for arthritis, constipation and coughs. This research investigated the effect of Kattosh stem extract (LSES) on streptozotocin‐induced damage to the pancreas, kidney, and liver using in vitro, in vivo and in silico methods. In vitro phytochemical, antioxidative and anti‐inflammatory effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 46 publications
1
11
0
Order By: Relevance
“…A lot of medicinal plants are used in traditional medicine all over the world to reduce pain and treat hyperthermia; they can also play a vital role in counteracting oxidation and cytotoxicity in cells. 21 The The formalin-induced nociception model provides a longlasting pain with peripheral inflammation and central sensitization. 4 This protocol involves a biphasic reaction consisting of an early (neurogenic) phase and a late (inflammatory) phase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A lot of medicinal plants are used in traditional medicine all over the world to reduce pain and treat hyperthermia; they can also play a vital role in counteracting oxidation and cytotoxicity in cells. 21 The The formalin-induced nociception model provides a longlasting pain with peripheral inflammation and central sensitization. 4 This protocol involves a biphasic reaction consisting of an early (neurogenic) phase and a late (inflammatory) phase.…”
Section: Discussionmentioning
confidence: 99%
“…A lot of medicinal plants are used in traditional medicine all over the world to reduce pain and treat hyperthermia; they can also play a vital role in counteracting oxidation and cytotoxicity in cells. 21 The present study was designed to investigate the anti‐nociceptive, antipyretic, antioxidant and cytotoxic effects of a methanol extract of C. velutina bark on pain stimulation. Pain is currently a major global health issue evident as headaches, cancer, inflammation, arthritis, osteoporosis and fever.…”
Section: Discussionmentioning
confidence: 99%
“…Following administration, meals were withdrawn for 3–4 h. The mortality and motor behavior for morbidity of the treated groups were observed for 24 h. Different parameters were carefully observed such as skin and fur, eyes, tremor, diarrhea, convulsions, salivation, mucous membranes, lethargy, respiration, behavior pattern, allergic syndromes, etc. The median fatal dose (LD 50 > 2.0 g/kg) was employed, as an effective therapeutic dose [ 13 ].…”
Section: Methodsmentioning
confidence: 99%
“…Next, STZ (60 mg/kg b.w. ), dissolved in 0.1 M citrate buffer (pH 4.5), was injected intraperitoneally to all groups, but only citrate buffer was injected to the normal control group according to Mostafavinia [ 13 , 14 ]. STZ, being a potential β-cell toxin, induces partial β-cell dysfunction, and thus, induces type 2 diabetes.…”
Section: Methodsmentioning
confidence: 99%
“…We previously demonstrated that isoflavone protects from kidney injury in obese animals via PPAR-γ [14], prevents bone loss in ovariectomized diabetic animals [15], and can attenuate the effects of vulvovaginal atrophy in women [16]. Taking into account the protective function of PPAR-γ in kidney injury [17][18][19][20], the objective of this work was to evaluate the effect of ovariectomy and the consequent gonadal failure on the development of DM1induced kidney injury, as well as the contribution of soy isoflavone via PPAR-γ in this experimental animal model. Our hypothesis is that gonadal failure potentiates renal injury induced by chronic hyperglycemia and that isoflavone treatment attenuates this condition by PPAR-γ induction.…”
Section: Introductionmentioning
confidence: 99%